2000
DOI: 10.1038/sj.onc.1203769
|View full text |Cite
|
Sign up to set email alerts
|

Lack of p19INK4d in human testicular germ-cell tumours contrasts with high expression during normal spermatogenesis

Abstract: p19 INK4d , a member of the INK4 family of cyclindependent kinase inhibitors, negatively regulates the proto-oncogenic cyclin D/CDK4(6) complexes whose ability to phosphorylate the retinoblastoma tumour suppressor (RB) promotes G1/S transition. In contrast to the related p16 INK4a tumour suppressor, expression patterns of 19 INK4d in human tissues and tumours remain unknown. As the RB pathway is commonly targeted in cancer, and mouse models suggest a role for p19 INK4d in spermatogenesis, we examined the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 33 publications
6
46
0
1
Order By: Relevance
“…As in our data, CDKN2d (p19 INK4d ) has also been found to be lost in testicular germ cell tumors contrasting its high expression in normal spermatogenesis. 21 We detected meiotic induction of cyclin A1 and CDK2, which are essential for spermatogenesis but not for mitosis. [9][10][11][12] CDKN2c (p18 INK4c ) and CDKN2d (p19 INK4d ), whose expression also markedly increased, conferred infertility to double-knockout mice.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As in our data, CDKN2d (p19 INK4d ) has also been found to be lost in testicular germ cell tumors contrasting its high expression in normal spermatogenesis. 21 We detected meiotic induction of cyclin A1 and CDK2, which are essential for spermatogenesis but not for mitosis. [9][10][11][12] CDKN2c (p18 INK4c ) and CDKN2d (p19 INK4d ), whose expression also markedly increased, conferred infertility to double-knockout mice.…”
Section: Discussionmentioning
confidence: 86%
“…We created transgenic mice that expressed both b-galactosidase and EGFP under the control of the murine and the human cyclin A1 promoter, respectively. 12,14,26 Expression of the reporter genes was then analyzed in adjacent testis sections prepared from mice at postnatal days 1,4,8,11,14,18,21,26 and 34 by X-gal staining (b-galactosidase) and fluorescence microscopy (EGFP; Fig. 6a).…”
Section: Human and Murine Cyclin A1 Promoter Activity In Testis Develmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of tumour suppressor genes have been recognised for which epigenetic silencing is the predominant mechanism of gene inactivation and for which somatic mutations are rare. While several testicular tumour suppressor genes have now been identified (Bartkova et al, 2000;Datta et al, 2001;Luo et al, 2001;Eyzaguirre and Gatalica, 2002;Honorio et al, 2003), only a few, for example RASSF1A (Honorio et al, 2003), MGMT (SmithSorensen et al, 2002), have been reported to be silenced in testicular tumours through DNA hypermethylation.…”
mentioning
confidence: 99%
“…Although several reports have examined expression of isolated G1-S-phase regulators in arrested and apparently cycling germ cells [14,15], an important limitation of these studies is the lack of a comprehensive and direct comparison of the G1-S-phase cell cycle regulators in cells shown to be undergoing mitotic arrest. Interestingly, it has been shown that common molecular abnormalities found in testis cancer include mutations in some regulators of the G1-S-phase of the cell cycle [16]. Defining the normal function of these genes in the cell cycle of developing germ cells promises to ultimately increase our understanding of testis cancer.…”
Section: Introductionmentioning
confidence: 99%